Digital Banking As An Online Transaction Service For Customer Satisfaction - Nurhidayah Layoo; Nurmawati Mambuhu (International Forum of Researchers and Lecturers, 2022)
The increased garbage creation in Maros may motivate businesses to become more concerned with environmental sustainability. Armour Coffee's green marketing strategy begins with the brand logo and extends to the firm's vision and objective. According to statistics from the top brand index, Armour Coffee remains the least popular local coffee shop in Indonesia, which is both a phenomena and a problem in this study. Based on the findings, the study concludes that Green Product and Green Place have a favourable influence on Interest in Purchasing Armour Coffee in Maros. Meanwhile, Green Price and Green Promotion had little influence on Interest in Purchasing Armour Coffee in Maros. Simultaneously, green product, green pricing, green location, and green promotion (green marketing mix) impact interest in purchasing Armour Coffee in Maros.